Evaporation of Suspended Heavy Oil/1-Pentanol Droplets in Flame-like Conditions - Poonawala, Taha; Asrardel, Mohamad; Muelas, Álvaro; Ballester, Javier (Jornada de Jóvenes Investigadores del I3A, 2023)
In this work high temperature evaporation characteristics of isolated, suspended, ≈500 µm size droplets of heavy fuel oil/1-pentanol blends are experimentally studied. Flame-like ambient conditions are reproduced by developing a new suspended droplet facility such that the influence of major external effects is minimum.